2021
DOI: 10.1177/1098612x21994396
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CT features of 79 cats with intranasal mass lesions

Abstract: Objectives This retrospective multicentre study compared the CT characteristics of cats diagnosed with intranasal mass lesions to determine if defining imaging features exist between different tumour types and between neoplastic and non-neoplastic lesions. Methods The medical records of two institutions were reviewed for cats with CT findings consistent with an intranasal mass lesion with subsequent histopathological examination. For each CT scan the mass location, growth pattern, margin distinction, contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 19 publications
(54 reference statements)
1
15
0
3
Order By: Relevance
“…Extra‐neural tissue infiltration was observed in >40% of cats with intracranial lesions, with a permeative to moth‐eaten bone lysis growth pattern, leaving residual bone in situ with a preserved bone shape. This type of growth pattern recently has been described in cats with nasal lymphoma and carcinoma 39 . Although intracranial infiltration via the cribriform plate has been described in 7% to 34% of cats with nasal lymphoma, 39‐41 to our knowledge ours is the first description of the peculiar infiltration of the rostral leptomeninges and olfactory lobes, associated with intralesional hemorrhages.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Extra‐neural tissue infiltration was observed in >40% of cats with intracranial lesions, with a permeative to moth‐eaten bone lysis growth pattern, leaving residual bone in situ with a preserved bone shape. This type of growth pattern recently has been described in cats with nasal lymphoma and carcinoma 39 . Although intracranial infiltration via the cribriform plate has been described in 7% to 34% of cats with nasal lymphoma, 39‐41 to our knowledge ours is the first description of the peculiar infiltration of the rostral leptomeninges and olfactory lobes, associated with intralesional hemorrhages.…”
Section: Discussionsupporting
confidence: 54%
“…39 Although intracranial infiltration via the cribriform plate has been described in 7% to 34% of cats with nasal lymphoma, [39][40][41] to our knowledge ours is the first description of the peculiar infiltration of the rostral leptomeninges and olfactory lobes, associated with intralesional hemorrhages. The combination of this type of bone, leptomeningeal, and olfactory lobes infiltrative pattern on MRI may help to differentiate lymphoma from other neoplasms centered on the cribriform plate, such as nasal carcinomas, 39,40,42 esthesioneuroblastoma, 43 histiocytic sarcoma, 44 meningioma, 45 or from granulomatous rhinitis. 39,46 In contrast to brain lesions, bone lysis was not observed in our group of cats with spinal lesions, even in the presence of paravertebral lesions.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…At the time of this study, few published reports mention CT features in cases of nasal cryptococcosis and are limited to small number of dogs and cats (≤3). [4][5][6][7][8] In all studies, documenting CT features of nasal cryptococcosis was not the primary objective, thus descriptions of features are brief. In these select studies, CT features reported in cats include: soft tissue and fluid opacification in rostral nasopharynx and nasal cavities without a mass, intranasal mass, distinct nasopharyngeal (NP) mass, fluid opacification in nasal cavity and frontal sinus, and mass at nasal planum with focal lysis of nasal bone.…”
mentioning
confidence: 99%
“…In these select studies, CT features reported in cats include: soft tissue and fluid opacification in rostral nasopharynx and nasal cavities without a mass, intranasal mass, distinct nasopharyngeal (NP) mass, fluid opacification in nasal cavity and frontal sinus, and mass at nasal planum with focal lysis of nasal bone. [4][5][6][7] Reported CT features in dogs include lesions in nasal cavity, nasopharynx, and frontal sinus, osteomyelitis of frontal bones, lacrimal bones, and cribriform plate, and intracranial extension. 4,8 Characterization of CT features in dogs and cats with nasal cryptococcosis is important to better understand the utility of CT in the diagnosis of the disease and in the evaluation of chronic rhinitis in dogs and cats.…”
mentioning
confidence: 99%